Microtensile Bond Strength of Three Restorative Core Materials with IPS E.max Press Ceramic by Two Resin Cements - Mohammadi-bassir, Mahshid; Razavi, Seyyedeh Shaghayegh; Rezvani, Mohammad Bagher; Labbaf, Hossein (Journal of Dental School, 2019)
Objectives: The aim of this study was to compare the microtensile bond strengths (µ TBS) of three core materials with one lithium disilicate reinforced ceramic using two resin cements. Methods: Three core materials (Nulite F® (Biodental Technologies), Filtek Z250® (3M-ESPE), Prettau-Anterior® (Zirkonzhan, Germany)) were prepared as blocks (10×10×4 mm3) according to the manufacturer’s instructions. Lithium disilicate ceramic blocks were also constructed and bonded to core specimens with two dual curing luting resin cements (Duo-Link® (Schaumburg, IL), Bifix QM® (VOCO, Cuxhaven, Germany)). Micro-bar specimens were prepared and loaded in tension to determine the µ TBS Failure modes were classified by scanning electron microscope (SEM). Data were analysed using two-way ANOVA and Tukey HSD test. Results: The µ TBS varied significantly depending on the core materials and resin cements used (P< 0.05). The µ TBS of Bifix QM was significantly higher than of Duo-Link in all core materials. The µ TBS of zirconia core was significantly higher than of both composite cores with both resin cements. There were no statistically significant differences among Nulite F and Filtek Z250 (P> 0.05). The highest bond strength was obtained between zirconia core and Bifix QM (45.3 ± 6.7 MPa). Conclusion: In vitro µ TBS of glass ceramic blocks bonded to zirconia core material showed higher bond strength values than resin-based core material, regardless of the resin cement type used.